Goal! : the dream begins - Rigby, Robert (Orlando, Fla. : Harcourt, 2006)
Santiago, a young Mexican American, fulfills his dream of playing soccer when a chance encounter in inner-city Los Angeles results in a trip to England to try out for the Newcastle United soccer team.
Originally published: United Kingdom : Corgi Books, 2005.
"Official movie tie-in novelization"--Cover.
Ages 12 and up.
Keywords: Newcastle United Football Club -- Juvenile fiction; Soccer stories; Mexican Americans -- Juvenile fiction; England -- Juvenile fiction